Cartographic perspectives on spatial and thematic levels of detail in augmented reality: a review of existing approaches - Anastopoulou, Niki; Kokla, Margarita; Tomai, Eleni; Cheliotis, Kostas; Liarokapis, Fotis; Pastra, Katerina; Kavouras, Marinos (My University, 2023)
Augmented reality (AR) is a rapidly advancing technology that enhances users’ perception of the real world by overlaying virtual elements. The geospatial community has been gradually focusing on AR because of its ability to create immersive spatial experiences and facilitate spatial learning. However, designing effective AR interfaces poses several challenges, including managing information overload, providing intuitive user interaction, and optimizing system performance. The management of the Level of Detail (LoD) is a crucial part of an AR-enhanced cartographic representations as it can greatly impact the quantity, accuracy, and usefulness of the information being conveyed and enhance the readability and usability of an application. In this paper, we present a systematic review of published research on the management of LoD for AR cartographic representations based on various dimensions that focus on the types of data that are visualized, the techniques used, and the user actions that trigger LoD change. A corpus of fifteen scientific papers involving different LoD management techniques within AR environments have been analyzed. The limited number of papers implies that this kind of applications is in its infancy. The review provides a synthesis of existing knowledge and identifies challenges for future research in this exciting and dynamic field.
Keywords: 3D geovisualization; Augmented reality; cartographic generalization; thematic level of detail; spatial level of detail